Comparison of conventional and heat balance based energy analyses of steam turbine - Medica-Viola, Vedran (Array, 2020)
This paper presents a comparison of conventional and heat balance based energy analyses of steam turbine. Both analyses are compared by using measured operating parameters from low power steam turbine exploitation. The major disadvantage of conventional steam turbine energy analysis is that extracted energy flow streams are not equal in real (polytropic) and ideal (isentropic) expansion processes, while the heat balance based energy analysis successfully resolved mentioned problem. Heat balance based energy analysis require an increase of steam mass flow rates extracted from the turbine in ideal (isentropic) expansion process to ensure always the same energy flow streams to all steam consumers. Increase in steam mass flow rate extracted through each turbine extraction (heat balance based energy analysis) result with a decrease in energy power losses and with an increase in energy efficiency of whole turbine and all of its cylinders (when compared to conventional analysis). All of the obtained conclusions in this research are valid not only for the analyzed low power steam turbine, but also for any other steam turbine with steam extractions.